Efektivitas Penggunaan Anggaran Di Pusat Kesehatan Masyarakat Gelumbang Kabupaten Muara Enim - Merryati, Merryati; Novaria, Eva; Sandy, Amiruddin (@-Publik: Jurnal Administrasi Publik, 2025)
The Gelumbang District Muara Enim Community Health Center, in terms of budget utilization, strives to use the available budget in accordance with the applicable regulations, to ensure the smooth operation of the Gelumbang Community Health Center, in order to provide the best possible service to the service users. The issues arising in the budget utilization at the Gelumbang District Muara Enim Community Health Center are caused by several factors, resulting in the addition of unutilized funds (known as "silpa"). These factors include: 1) The remaining budget from the previous year and increased income from the Health Social Security Agency (BPJS Kesehatan), which makes payments to First-Level Health Facilities (FKTP) based on the capitation for the registered participants in the FKTP. 2) A lack of employees with the necessary skills and qualifications. 3) Changes in financial management regulations to become a Regional Public Service Agency (BLUD). The aim of this study is to analyze the effectiveness of budget utilization at the Gelumbang District Muara Enim Community Health Center. Based on the research results, it is known that the implementation of human resources is effective, even though they have to take on double roles. The infrastructure is also effective as it meets the requirements, and the budget utilization is effective every year in line with the targets. The alignment of budget utilization is effective because it adheres to the work plan, budget, and the relevant regulations. However, the absorption of the budget is not yet effective due to the existence of unutilized funds, but financial reporting is effective and timely.